Production of Bio-Ethanol from Iraq Date Crop - Shahad, Dr. Haroun A. K.; Ebraheem, Adnan Kahtan (Journal of Petroleum Research and Studies, 2017)
This research studied the possibility of producing bio-ethanol from Iraqi date crop. The juice of the Zahdi species of Iraqi dates is chosen for this purpose since it is available in large quantities in Iraq and has good sugar contents. The production procedure consists of fermentation, distillation and dehydration processes. A special rig is designed and assembled for the production. The fermentation process involved the use of three different types of yeast (the bread yeast, cheese Yeast and whey) to choose the best type that requires shorter fermentation time. It is found that the fermentation times for these yeasts are 25, 40 and 34 hrs respectively. The fermentation process is followed by the distillation process, which was performed in three stages. Finally, the dehydration process which is the most important and difficult process because it takes a long time to produce the required concentration of ethanol. This process involved the use of two different types of drying materials (ethylene glycol and calcium oxide). Experimental results show the importance of using dates as a source of bio ethanol in Iraq. It is found that 1 ton of Zahdi yields 300 L of bio-ethanol. It is also found that the cost of 1 L bio-ethanol is about 1022 ID which is about 85 cents. This cost can be reduced in case of mass production. This price is comparable with ethanol prices worldwide. This work proved that date crop in Iraq is an important source of renewable energy comparable to crude oil.